TATALAKSANA EKLAMSIA PASCA SECTIO CAESARIA - Arief Kurniawan; Nur Pudyastuti Pratiwi (Journal of Innovation Research and Knowledge, 2023)
Hypertension in pregnancy, including preeclampsia and eclampsia, is one of the complications that contribute to a significant level of morbidity and mortality. Eclampsia is a manifestation of seizures from hypertensive pregnancy, is the main cause of maternal death, and can occur before, during, or after delivery. The purpose of this case report is to describe a case of eclampsia that occurred postpartum. The patient, who was referred to Dustira Cimahi Hospital with complaints of discharge from the birth canal, was diagnosed with G1P0A0, Parturient Preterm Stage 1 Latent Phase, Gemelli, and Premature Rupture of the Membranes. The results of the examination showed hypertension and thrombocytopenia. The patient underwent a caesarian section under regional anesthesia. Both babies were born alive with normal conditions. The patient then experienced visual disturbances such as being unable to see and experiencing 3 times tonic-clonic seizures with a duration of 1 minute for each seizure. The patient was diagnosed with Post SC Eclampsia and Preeclampsia with Severe Symptoms. The patient was treated in the ICU with miloz, perdipine, ceftriaxone, mannitol, dexamethasone, citicoline, omeprazole, phenytoin, and kaltrofen. Oxygen therapy is given through noninvasive ventilation, followed by a facemask and a nasal cannula because her consciousness and breathing have improved. The key management of eclampsia is preventing maternal injury, placing the lateral decubitus position, oxygen support, monitoring vital signs, and other supportive measures.